Policy challenges towards potential climate change impacts: In search of agro-climate stability - Al-Amin, A.Q.; Azam, M.N.; Yeasmin, M.; Kari, F. (Academic Journals, 2010)
This study focuses on climate-related vulnerability for Malaysian agriculture. We use an analysis of impacts based on observational records of inter-annual variability in precipitation and warming climatic factors. The assessment involved General Circulation Models (GCMs) together with the Stern Review study to represent a range of plausible climate scenarios and economic outcomes. This study investigates the major Malaysian agricultural sectors such as food crops (that is, rice) and cash or industrial crops (i.e. palm oil and rubber) under a climatic and economic perspective, quantifying the merits of the projected simulation and presenting an insight into the nature of the overall subject of suitability of adaptation options. These analyses signify the likely future changes to agriculture, potential strategies to reduce vulnerabilities and reveal adaptation requirements for agriculture. The findings of this study can be used for climate-related national policy on agriculture in Malaysia.